Demographic analysis demonstrates systematic but independent spatial variation in abiotic and biotic stressors across 59 percent of a global species range. (9th October 2017) - Ruskin, Katharine J.; Etterson, Matthew A.; Hodgman, Thomas P.; Borowske, Alyssa C.; Cohen, Jonathan B.; Elphick, Chris S.; Field, Christopher R.; Longenecker, Rebecca A.; King, Erin; Kocek, Alison R.; Kovach, Adrienne I.; O'Brien, Kathleen M.; et al.
Abstract: The balance of abiotic and biotic stressors experienced by a species likely varies across its range, resulting in spatially heterogeneous limitations on the species' demographic rates. Support for spatial variation in stressors (often latitudinal gradients) has been found in many species, usually with physiological or correlative occupancy data, but it has rarely been estimated directly with demographic data. We collected demographic data from 23 sites spanning the majority of the Saltmarsh Sparrow ( Ammodramus caudacutus ) breeding range. Using data from 837 nests, we quantified the abiotic and biotic variables most important to nest survival, which is the dominant driver of both fecundity and population growth rate in this species. We separately estimated daily nest failure probability due to nest depredation (biotic stressor) and nest flooding (abiotic stressor), which collectively account for almost all nest failure in the species. Nest depredation decreased with latitude, whereas nest flooding was not related to latitude. Instead, nest flooding was best predicted by a combination of maximum high tide, extremity of rare flooding events, and date. For a single vital rate, we observed predictable variation in competing biotic and abiotic stressors across this species range. We observed that biotic and abiotic stressors were geographically independent, both on a large spatial scale and locally. Our results suggest that stressors on the fecundity of Saltmarsh Sparrow vary systematically across its range, but independently. The observed patterns of biotic and abiotic stress provide information for efforts to conserve the Saltmarsh Sparrow, which is considered threatened. Further, understanding the effects that different stressors, and their interactions, have on demographic rates is necessary to unravel the processes that govern species distributions and to effectively conserve biodiversity in the face of global change.